Precision-porous polyurethane elastomers engineered for application in pro-healing vascular grafts: Synthesis, fabrication and detailed biocompatibility assessment. (December 2021) - Zhen, Le; Creason, Sharon A.; Simonovsky, Felix I.; Snyder, Jessica M.; Lindhartsen, Sarah L.; Mecwan, Marvin M.; Johnson, Brian W.; Himmelfarb, Jonathan; Ratner, Buddy D.
Abstract: Unmet needs for small diameter, non-biologic vascular grafts and the less-than-ideal performance of medium diameter grafts suggest opportunities for major improvements. Biomaterials that are mechanically matched to native blood vessels, reduce the foreign body capsule (FBC) and demonstrate improved integration and healing are expected to improve graft performance. In this study, we developed biostable, crosslinked polyurethane formulations and used them to fabricate scaffolds with precision-engineered 40 μm pores. We matched the scaffold mechanical properties with those of native blood vessels by optimizing the polyurethane compositions. We hypothesized that such scaffolds promote healing and mitigate the FBC. To test our hypothesis, polyurethanes with 40 μm pores, 100 μm pores, and non-porous slabs were implanted subcutaneously in mice for 3 weeks, and then were examined histologically. Our results show that 40 μm porous scaffolds elicit the highest level of angiogenesis, cellularization, and the least severe foreign body capsule (based on a refined assessment method). This study presents the first biomaterial with tuned mechanical properties and a precision engineered porous structure optimized for healing, thus can be ideal for pro-healing vascular grafts and in situ vascular engineering. In addition, these scaffolds may have wide applications in tissue engineering, drug delivery, and implantable device.